The Relationship between the Implementation of Standard Operating Procedures (SOP) and the Risk of Accidents in Anchor Handling Work on the Anchor Handling, Tug, Supply (AHTS) Vessel Owned by PT. Logindo Samudramakmur TBK. - Vensha Pratama Annurransyah; Iie Suwondo; Firdaus Sitepu; Intan Sianturi (International Journal of Science and Environment (IJSE), 2026)
This study examines the relationship between the implementation of Standard Operating Procedures (SOPs) and the risk of accidents in anchor handling work on Anchor Handling, Tug, and Supply (AHTS) vessels owned by PT. Logindo Samudramakmur Tbk. The objectives of the study were to determine the level of accident risk and analyze the effect of SOP compliance on the risk. The research method used was quantitative with a survey design, complemented by descriptive analysis and simple linear regression. The population consisted of all deck crews involved in anchor handling work on three AHTS vessels (Logindo Enterprise, Logindo Energy, Logindo Stamina), with a total sample of 27 respondents through census techniques. Primary data were collected using a closed questionnaire that was tested for validity and reliability, then analyzed using SPSS version 26. The results showed that the risk of accidents was quite high (average 45.52 out of 50), while the implementation of SOPs was considered good (average 43.81). Pearson correlation yielded a very strong and significant negative relationship (r = 0.946, p < 0.05), with 89.4% of the risk variation explained by the regression model Ŷ = 11.824 + 0.769X. The study concluded that consistent SOP compliance significantly reduces the risk of accidents and strengthening SOPs as a safety culture is crucial for AHTS operational safety.